Die Mixing Memory and Desire. - Ammann, Jean-Christophe; Basualdo, Carlos; Baumgartner, Marcel; Bee, Andreas; Benslama, Fehti; Bergson, Henri; Blazwick, Iwona; Bryson, Norman; Cardiff, Janet; Chapuis, Yvane; Cooke, Lynne; Dean, Tacita; et al. (Luzern : Kunstmuseum Luzern, 2000)
Desire - wunsch is the first volume of the catalogue for the exhibition Mixing Memory and Desire - Wunsch und Erinnerung, the opening exhibition of the new Museum of Art Lucerne. It brings together textual and visual documentation on the participating artists along with excerpts from foundational theoretical texts of the twentieth century. A selection of materials is thus made available which the exhibition's curators, Ulrich Loock, Daniel Kurjakovic, Cornelia Dietschi and Yvane Chapuis, used for their preparations. In her essay The Great Silk Road, the Russian author Ivetta Gerasimchuk unfolds the history and economy of silk-spinning as an allegory for the process of artistic production on the basis of doubt.
Alÿs, Francis ; Beecroft, Vanessa ; Cardiff, Janet ; Castres, Edouard ; Coste, Annelise ; Dean, Tacita ; Diogg, Felix Maria ; Döbeli, Markus ; Dumas, Marlene ; Gérald ; Gordon, Douglas ; Havekost, Eberhard ; Huws, Bethan ; De Keyser, Raoul ; Khattari, Majida ; Krijnen, Cees ; Lehanka, Marko ; Leroy, Xavier ; Marden, Brice ; Motti, Gianni ; Mucha, Reinhard ; Perigot, Alexandre ; Pistoletto, Michelangelo ; Ray, Charles ; Reinhart, Joseph ; Schiess, Adrian ; Schneider, Gregor ; Segal, Miri ; Smith/Stewart ; Triozzi, Claudia ; Walker, Aldo ; Wall, Jeff ; Welling, James ; West, Franz ; Wool, Christopher ; Wyrsch, Johann Melchior ; Zünd, Robert
Duits & Engels
Mixing Memory and Desire / Wunsch und Erinnerung, Kunstmuseum Luzern, 20. Juni bis 24. September 2000. Curated by Ulrich Loock, Daniel Kurjakovic and Cornelia Dietschi.
boek